2000
DOI: 10.1002/(sici)1097-4652(200002)182:2<196::aid-jcp8>3.0.co;2-e
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of prostaglandin E2 receptors and their role in 24,25-(OH)2D3-mediated effects on resting zone chondrocytes

Abstract: Resting zone chondrocyte differentiation is modulated by the vitamin D metabolite, 24,25-(OH)(2)D(3), via activation of protein kinase C (PKC). In previous studies, inhibition of prostaglandin production with indomethacin caused an increase in PKC activity, suggesting that changes in prostaglandin levels may mediate the 24, 25-(OH)(2)D(3)-dependent response and act as autocrine or paracrine regulators of chondrocyte metabolism. Supporting this hypothesis is the fact that resting zone cells respond directly to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
15
0

Year Published

2001
2001
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 41 publications
(16 citation statements)
references
References 43 publications
1
15
0
Order By: Relevance
“…However, we have not observed any involvement of EP2 receptor in PGE 2 ‐induced suppression of MMP‐1 release in HCS‐2/8 chondrocytes. Previous studies have shown the presence of both EP2 and EP4 receptors in chondrocytes [Del Toro et al, 2000; Miyamoto et al, 2003]. We have also demonstrated that in HCS‐2/8 chondrocytes EP2 receptor is implicated in TNF‐α‐stimulated release of m‐calpain [Fushimi et al, 2004].…”
Section: Discussionsupporting
confidence: 70%
See 2 more Smart Citations
“…However, we have not observed any involvement of EP2 receptor in PGE 2 ‐induced suppression of MMP‐1 release in HCS‐2/8 chondrocytes. Previous studies have shown the presence of both EP2 and EP4 receptors in chondrocytes [Del Toro et al, 2000; Miyamoto et al, 2003]. We have also demonstrated that in HCS‐2/8 chondrocytes EP2 receptor is implicated in TNF‐α‐stimulated release of m‐calpain [Fushimi et al, 2004].…”
Section: Discussionsupporting
confidence: 70%
“…PGE 2 was initially identified as a molecule, which stimulated bone resorption [Klein and Raisz, 1970]. In contrast, several studies have demonstrated that PGE 2 plays a key role in chondrocyte differentiation [Del Toro et al, 2000; Miyamoto et al, 2003]. Moreover, recent studies indicate that PGE 2 stimulates [Nishikawa et al, 2002] or downregulates [Case et al, 1990; Pillinger et al, 2003] the induction of MMPs.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Thus, Cox‐1 may contribute to the rapid increase in PKC that occurs in response to 1α,25‐(OH) 2 D 3 activation of the 1α,25‐(OH) 2 D 3 membrane vitamin D receptor by metabolizing arachidonic acid released by PLA 2 over the first 5 min [Schwartz and Boyan, 1988] and at the same time contributing to the downregulation of the rapid response. The PGE 2 produced as a consequence of the action of Cox‐1 can then act through its EP‐1 receptor [Del Toro et al, 2000] to amplify the rapid effects of 1α,25‐(OH) 2 D 3 on PKC. 1α,25‐(OH) 2 D 3 also induces new PKC expression and incorporation of PKCα into plasma membranes and PKCξ into matrix vesicles within 24 h of exposure to the hormone [Sylvia et al, 1996].…”
Section: Discussionmentioning
confidence: 99%
“…1α,25‐(OH) 2 D 3 causes a rise in the production of both prostaglandin E 1 (PGE 1 ) and prostaglandin E 2 (PGE 2 ) [Schwartz et al, 1992], and inhibition of prostaglandin production by indomethacin reduces the stimulatory effects of 1α,25‐(OH) 2 D 3 on PKC activity. Exogenous PGE 2 regulates PKC activity through the EP1 receptor present on growth zone cells [Del Toro et al, 2000].…”
mentioning
confidence: 99%